Blood in the Corridor: The Digital Mastery of Hero Run Shoot-outs in Kick-Ass and Wanted. Issue 1 (2nd January 2017) - Bender, Stuart; Palmer, Lorrie
ABSTRACT: This article examines the significance of the digital aesthetic of violence in the uniquely contemporary action-film "hero run" shoot-out sequences. By using the case studies of Kick-Ass (2010) and Wanted (2008), the article focuses on how the particular stylistic tendencies of these sequences display a link between the onscreen, digital-enabled mastery of the shooter with the offscreen digital mastery of the visual-effects artist.